PREDICTION OF VISCOSITY AND IONIC CONDUCTIVITY OF IMIDAZOLIUM-BASED IONIC LIQUIDS AT DIFFERENT TEMPERATURES USING A QUANTITATIVE STRUCTURE-PROPERTY RELATIONSHIP APPROACH - KOI , ZI KANG (2021)
Ionic liquids (ILs) have been widely explored in various industrial processes and applications because of their remarkable features besides being regarded as promising and environmentally friendly solvents. Nevertheless, it requires a huge effort to find the proper combinations of cations and anions in formulating ILs with desired properties. Thus, the development of a simple and accurate model to predict the physicochemical properties of ILs is of high interest. Notably, both viscosity and ionic conductivity are considered crucial physical properties which affect the transport capabilities of ILs and remain as one of the barriers in the design of suitable ILs.